Determination of shelf life of four herbal medicinal products using high-performance liquid chromatography analyses of markers and the Systat Sigmaplot software - Doris Kumadoh, Kwabena Ofori Kwakye, Noble Kuntworbe, Ofosua Adi-Dako, James Addy Appenahier (Journal of Applied Pharmaceutical Science, 2020)
Shelf life determination of herbal medicines is of paramount importance as it relates to activity of constituents of the product. This work sought to determine shelf life of four herbal products (Nibima, Asena, Lippia tea, and NPK 500 capsules). The method involved the determination of marker content of products (three batches each) at time points (0, 3, 6, 9, 12, and 18 months) at storage temperature and humidity of 30°C ± 2°C/70% RH ± 5% RH using high-performance liquid chromatography (HPLC) analyses. Batch blending was employed for preparation of reference samples of products. In UV analyses, λmax of 289, 291, 327, and 289 nm were obtained from spectra for (Nibima, Asena, Lippia tea, and NPK 500 capsules, respectively. A common 230 nm UV marker was observed for all the products. Optimized HPLC conditions were developed for products using methanol: water: 0.1%v/v acetic acid system with mobile phase ratios of 9:0:1 (Nibima), 7:2:1 (Asena), 8:1:1 (Lippia tea), and 90:5:5 (NPK 500 capsules). Wavelength of detection used for HPLC analyses were 283, 290, 332, and 290 nm for Nibima, Asena, Lippia tea, and NPK 500 capsules, respectively. HPLC marker content analyses with time produced shelf life of 23.14, 21.16, 62.97 and 32.91 months for Nibima, Asena, Lippia tea, and NPK 500 capsules, respectively. Obtained shelf life indicates relative stability of products.
Keywords: Stability, shelf life, markers, herbal products, UV-Vis Spectroscopy, HPLC.